An exploration of the restandardization of Sepedi : the inclusion of the Khelobedu dialect - Malatji, Mmatlou Jerida (My University, 2017)
The study explored the restandardization of Sepedi with the aspiration of including Khelobedu dialectical lexicons in the standard form. The standardization of Sepedi, unlike the case of Shona, excluded many of its dialects from the process, thus, left Khelobedu speakers outside of this medium and later subjected them to learn it in schools, putting them at a point of disadvantage academically. Very few studies have been conducted around this term restandardization. This study is mixed method in approach and sequential in design. Data is collected via self-administered questionnaires and face-to-face interviews using an interview guide. A total of 20 participants from four villages in the Mopani District made up a sample for the quantitative data collection phase, while four participants who are Language practitioners by profession made up the qualitative phase of the study. The findings of the study reveal that dialect speakers do not have much confidence in their dialectical variety. They still believe that English and Sepedi are mediums of development and progress. Although restandardization according to the language practitioners is said to possible, PanSALB still has a lot to do in terms of developing Indigenous Languages in South Africa.
Thesis ( M. A. (Translation Studies and Linguistics)) -- University of Limpopo, 2017
Keywords: Khelobedu language; Dialectical lexicons; Indigenous Languages; Sepedi language -- Standardization; Sepedi language -- Dialects; Standardization